Exploiting nutrient-microbe synergy in unlocking productivity potential of perennial fruits : A review - SRIVASTAVA, A K; MALHOTRA, S K; KUMAR, N K KRISHNA (The Indian Journal of Agricultural Sciences, 2015)
Fruits crops by the virtue of their nutritional qualities have already emerged as a major alternative, cutting short the menacing load on the consumption of traditional monotonous cereal/tuber crop-based diet. Huge microbial diversity has displayed different magnitude of synergism with fruit crops, which played a catalytic role in unlocking the productivity stagnation through improved efficacy of applied nutrients. Perennial fruit crops are better equipped to be benefitted through nutrient-microbe synergy because of their perennial framework and root configuration. However, use of multiple inoculation through crop specific microbial consortium, especially AM-based consortium in combination with nutrients (organic or inorganic in nature) provided a much better option in fruits with an added element of much better labile pool of microbial (taxonomic, function, and metabolic diversity) and nutrient pool of the rhizosphere for stronger soil carbon sink ultimately. The concept of “rhizosphere hybridization” is, therefore, advocated to harness the value added benefit of nutrient -microbe synergy, besides providing dynamism to microbial consortium suiting to wide range of perennial fruits. Microbial consortium augers well, with fertigation option as well, as a pretreatment of soil before injecting soluble mineral fertilizers into the wetting zone of drippers in order to improve upon the fertilizer use efficiency.